Efficacy of inferior turbinate reduction in pediatric patients: a prospective analysis. Issue 12 (16th June 2021) - Whelan, Rachel L.; Shaffer, Amber D.; Stapleton, Amanda L.
Abstract: Background: Chronic nasal congestion is a common presentation in the pediatric setting. For patients who fail to respond to maximal medical therapy and adenoidectomy, inferior turbinate reduction (ITR) may be a reasonable adjuvant surgical approach. Our objective was to prospectively evaluate nasal congestion symptoms and daily medication use in the year following ITR in children with and without allergic rhinitis (AR). Methods: Patients younger than 18 years undergoing ITR alone or in combination with nonsinonasal procedures were enrolled. Scores from the Nasal Obstruction Symptom Evaluation (NOSE) survey were collected preoperatively and at 3, 6, and 12 months postoperatively from 96 patients. Number and type of pertinent daily medications utilized were also analyzed using Wilcoxon signed‐rank and McNemar's tests. Patients with and without comorbid AR were then compared using Wilcoxon rank‐sum tests. Results: Median (range) NOSE sum scores significantly improved from preoperative median of 65 out of 100 points (0–100) to 20 (0–100), (z = 7.12, p < 0.001) at 12 months postoperatively. The median number of daily medications was significantly reduced from 1 (range, 0–4) preoperatively to 0 (range, 0–5) postoperatively (z = 2.38, p = 0.017). Fifty‐six (58.3%) patients had AR. AR patients received more medications preoperatively and postoperatively compared with those without AR (z = −2.96, p = 0.003; z = −2.23, p = 0.024). At 12 months, NOSE scores remained significantly greater in patients with AR compared with those without AR (β = 11.6; 95% confidence interval [CI], 0.676–22.5; p = 0.038). Conclusion: Our data highlight the need for a multimodal approach to chronic nasal congestion, particularly in children with AR.